Chronic restraint stress induces sperm acrosome reaction and changes in testicular tyrosine phosphorylated proteins in rats - Supatcharee Arun; Jaturon Burawat; Wannisa Sukhorum; Apichakan Sampannang; Chanwit Maneenin; Sitthichai Iamsaard (Shahid Sadoughi University of Medical Science, Yazd, Iran, 2016)
Background: Stress is a cause of male infertility. Although sex hormones and sperm quality have been shown to be low in stress, sperm physiology and testicular functional proteins, such as phosphotyrosine proteins, have not been documented. Objective: To investigate the acrosome status and alterations of testicular proteins involved in spermatogenesis and testosterone synthesis in chronic stress in rats. Materials and Methods: In this experimental study, male rats were divided into 2 groups (control and chronic stress (CS), n=7). CS rats were immobilized (4 hr/day) for 42 consecutive days. The blood glucose level (BGL), corticosterone, testosterone, acrosome status, and histopathology were examined. The expressions of testicular steroidogenic acute regulatory (StAR), cytochrome P450 side chain cleavage (CYP11A1), and phosphorylated proteins were analyzed. Results: Results showed that BGL (71.25±2.22 vs. 95.60±3.36 mg/dl), corticosterone level (24.33±4.23 vs. 36.9±2.01 ng/ml), acrosome reacted sperm (3.25±1.55 vs. 17.71±5.03%), and sperm head abnormality (3.29±0.71 vs. 6.21±1.18%) were significantly higher in CS group in comparison with control. In contrast, seminal vesicle (0.41±0.05 vs. 0.24±0.07 g/100g), testosterone level (3.37±0.79 vs. 0.61±0.29 ng/ml), and sperm concentration (115.33±7.70 vs. 79.13±3.65×106 cells/ml) of CS were significantly lower (p<0.05) than controls. Some atrophic seminiferous tubules and low sperm mass were apparent in CS rats. The expression of CYP11A1 except StAR protein was markedly decreased in CS rats. In contrast, a 55 kDa phosphorylated protein was higher in CS testes. Conclusion: CS decreased the expression of CYP11A, resulting in decreased testosterone, and increased acrosome-reacted sperm, assumed to be the result of an increase of 55 kDa phosphorylated protein.